2017
DOI: 10.12688/f1000research.10534.1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with penicillin G and hydrocortisone reduces ALS-associated symptoms: a case series of three patients

Abstract: Three male Caucasian patients with ALS were admitted to the hospital due to progressive dysphagia and dysarthria. During two 21-day courses of penicillin G and hydrocortisone, these patients’ dysphagia and dysarthria resolved. The patient’s other ALS-associated symptoms also improved, including respiratory function, coordination, walking, and muscle strength. This is the first report of a treatment with a protocol for treating dysphagia, dysarthria, respiratory depression and other ALS-related symptoms. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Sun et al analyzed antibiotic use among 2,484 Swedish ALS patients and found an increased risk associated with all antibiotics, especially β-lactamase-sensitive penicillin ( 44 ). While these results suggest that the disruption of the protective microbiota might contribute to the disease pathogenesis, other studies showed a protective effect of penicillin ( 45 ). Such discrepancy in the influence of antibiotics on ALS pathogenicity is likely attributed to two factors: disruption of the protective microbiota and elimination of proteotoxic bacteria.…”
Section: Bacterial Infections Antibiotics and Protein Conformational ...mentioning
confidence: 83%
“…Sun et al analyzed antibiotic use among 2,484 Swedish ALS patients and found an increased risk associated with all antibiotics, especially β-lactamase-sensitive penicillin ( 44 ). While these results suggest that the disruption of the protective microbiota might contribute to the disease pathogenesis, other studies showed a protective effect of penicillin ( 45 ). Such discrepancy in the influence of antibiotics on ALS pathogenicity is likely attributed to two factors: disruption of the protective microbiota and elimination of proteotoxic bacteria.…”
Section: Bacterial Infections Antibiotics and Protein Conformational ...mentioning
confidence: 83%
“…Penicillin G/hydrocortisone may suppress gamma aminobutyric acid (GABA). In three Caucasian patients, it was reported that their symptoms were improved with the treatment ( Tuk et al, 2017 ). However, data from a 16-person phase 2 trial showed that it could not halt the progression of disease ( Van Es et al, 2020 ).…”
Section: Drugsmentioning
confidence: 99%
“…Of potential interest, Tuk cites one study in an ALS preclinical model utilizing glucocorticoids (21). In this study, mutant SOD1 mice were given either saline, the synthetic glucocorticoid steroid methylprednisolone in free form or methylprednisolone in a special molecular packaging.…”
Section: Preclinical Modelsmentioning
confidence: 99%
“…The only published case reports we found describing PALS without syphilis taking PNG/HC were the case series authored by Dr. Tuk (21). He describes three patients reportedly diagnosed with ALS at the Netherlands National ALS Center that were given at least two 21-day rounds of intravenous PNG with a 10-week break between infusions.…”
Section: Casesmentioning
confidence: 99%
See 1 more Smart Citation